Enhancement Quality of Particleboard from Oil Palm Trunk and Mahogany Sawdust with Layering of Talang Bamboo (Schizostachyum brachycladumc) - Hartono, Rudi; Fradika Oktavianus Bernadi Siahaan; Tito Sucipto; Erwinsyah; Jajang Sutiawan (Journal of Sylva Indonesiana, 2023)
Oil Palm Trunk (OPT) is a natural fiber used as an alternative material in wood-derived products such as particleboard. The OPT has low characteristics when using complete trunk, it is expected that its application would be a solution to reduce this plantation waste. In this investigation, the raw material of OPT particles was mixed with Mahogany, and Talang bamboo lamina to improve the physical and mechanical properties of the particleboard. This study aims to evaluate the addition of particleboard with various layerings of Talang Bamboo. The particleboard has three layers, with Talang bamboo (bamboo outer and inner part) on the face and back layers. There are six types of particleboard made: control, bamboo inner layering, bamboo outer layering, two bamboo inner layerings, two bamboo outer layerings, and a mixture of inner and outer bamboo layerings. The physical and mechanical properties of particleboard were testing according to JIS A 5908-2003 standard. The results of the physical properties showed that the density was 0.56-0.70 g/cm3, moisture content was 3.03-4.22%, water absorption was 52.01-87.15%, and thickness swelling was 11.62-24.68%. The mechanical properties showed MOE values was 9975.76-84246.63 kg/cm2, MOR was 81.64-670.77 kg/cm2, and IB was 0.91-3.38 kg/cm2. The physical and mechanical properties of particleboard met the JIS A 5908-2003 standard. According to this investigation's findings, Layering with the outer part of the Talang bamboo on the face and back of the particleboard is the best